MODEL PERALATAN PRAKTIKUM POMPA SENTRIFUGAL (PRACTICUM MODEL EQUIPMENT CENTRIFUGAL PUMP ) - Gunarto . (Universitas Muhammadiyah Pontianak, 2015)
Implementation of learning in engineering actually can not only through the theory in the classroom. Therefore, a good learning in the field of engineering is to add lab-based learning by improving laboratory facilities and infrastructure equipment, one of which is a fluid mechanics lab equipment. Current issues that especially the Faculty of Engineering Mechanical Engineering Study Program has not had a particularly fluid mechanics lab equipment for centrifugal pumps. Almost 75% of the world uses this equipment centrifugal pump. Therefore it is necessary to develop a model of learning media in the form of fluid mechanics lab equipment better is to develop instructional media lab equipment such as fluid mechanics models of centrifugal pumps. Research methodology using pure experimental design (true experimental research) conducted in the study were: Preparation and preparation of raw materials, reverse model lab equipment centrifugal pumps, testing tools and the use of tools for mechanics fluida. Research result, lab equipment that models these centrifugal pumps can be used for testing the characteristics of pumps in single, series and parallel. Keywords: centrifugal pumps, models, lab, serial, parallel ABSTRAKPelaksanaan pembelajaran di bidang teknik sebenarnya tidak bisa hanya melalui teori di dalam kelas. Oleh karena itu pembelajaran yang baik di bidang keteknikan adalah menambah pembelajaran berbasis laboratorium dengan meningkatkan sarana dan prasarana peralatan laboratorium, salah satunya adalah peralatan praktikum mekanika fluida. Permasalahan saat ini bahwa terutama Fakultas Teknik Program Studi Teknik Mesin belum memiliki peralatan praktikum mekanika fluida terutama untuk pompa sentrifugal. Hampir 75% masyarakat dunia menggunakan peralatan pompa sentrifugal ini. Oleh sebab itu perlu dikembangkan sebuah model media pembelajaran berupa peralatan praktikum mekanika fluida yang lebih baik yaitu mengembangkan media pembelajaran berupa model peralatan praktikum mekanika fluida pompa sentrifugal. Metodelogi penelitian menggunakan design eksperimen murni (true experimental research) yang dilakukan dalam penelitian adalah:preparasi dan persiapan bahan baku, merekayasa model peralatan praktikum pompa sentrifugal,pengujian alat dan penggunaan alat untuk praktikum mekanika fluida.Hasil penelitian, bahwa model peralatan praktikum pompa sentrifugal ini dapat digunakan untuk pengujian karakteristik pompa secara tunggal,seri dan paralel. Kata kunci: pompa sentrifugal, model, praktikum,seri,paralel